Successful pregnancies in patients with BCR‐ABL‐positive leukemias treated with interferon‐alpha therapy during the tyrosine kinase inhibitors era. (8th October 2018) - Balsat, Marie; Etienne, Madeleine; Elhamri, Mohamed; Hayette, Sandrine; Salles, Gilles; Thomas, Xavier
Abstract: Background: Management of pregnant patients with BCR‐ABL‐positive leukemia is challenging. Managing a patient who has been diagnosed while pregnant requires a different approach as compared to a patient who plans to become pregnant while on the treatment with tyrosine kinase inhibitor (TKI). Interferon (IFN)‐alpha is a useful option in both situations due to teratogenic potential of TKIs. Methods: We presented a series of 12 successful pregnancies in 11 women with BCR‐ABL‐positive leukemia, whose leukemia was managed with IFN‐alpha throughout their pregnancy. Results: All children have normal growth and development. All patients remained at least in hematological response and could start or resume TKI after delivery or breastfeeding. Conclusion: Because of the increased risk of teratogenicity and spontaneous abortion in female patient with pregnancy, when receiving TKI, IFN‐alpha can be considered a safe drug to be administered throughout pregnancy and could represent the drug of choice in this situation during the era of TKI therapy.